Geoinformation spatial analysis of the availability of natural heritage sites in a 100-km zone around Nizhny Novgorod (Russia) - Demyanchuk Anna; Astashin Andrej; Kamerilova Galina; Vatina Ol'ga; Podkovyrina Valeriya (E3S Web of Conferences)
The paper presents the results of a geoinformation spatial analysis of the availability of natural heritage sites in a 100-km zone around Nizhny Novgorod in order to identify promising areas and areas for the development of tourism and recreation. Landscape-recreational analysis was performed within the boundaries of landscape areas. The research is aimed at identifying the most promising areas for the development of nature-oriented types of tourism, which are most provided with natural heritage sites. For this reason, rather than administrative boundaries, the boundaries of landscape areas are taken as operational territorial units, since within their boundaries the morpholithogenic basis, climatic conditions, objects of the hydrographic network, soil and vegetation cover and faunal complexes naturally combine with each other, which determines the nature of natural heritage sites and their number.